We, the robots? : regulating artificial intelligence and the limits of the law - Chesterman, Simon (Cambridge : Cambridge University Press, 2021)
Should we regulate artificial intelligence? Can we? From self-driving cars and high-speed trading to algorithmic decision-making, the way we live, work, and play is increasingly dependent on AI systems that operate with diminishing human intervention. These fast, autonomous, and opaque machines offer great benefits - and pose significant risks. This book examines how our laws are dealing with AI, as well as what additional rules and institutions are needed - including the role that AI might play in regulating itself. Drawing on diverse technologies and examples from around the world, the book offers lessons on how to manage risk, draw red lines, and preserve the legitimacy of public authority. Though the prospect of AI pushing beyond the limits of the law may seem remote, these measures are useful now - and will be essential if it ever does.
Introduction -- Speed -- Autonomy -- Opacity -- Responsibility -- Transparency -- New Rules -- New Institutions -- Regulation byAI? -- Conclusion : We, the Robots?
Title from publisher's bibliographic system (viewed on 21 Jul 2021).
Keywords: Artificial intelligence -- Law and legislation